Changes in micronutrient status on submergence of basmati growing soils of Jammu - AKBAR, ALI; MONDA, A. K.; WALI, PARDEEP ,; RAI, A. P.; RAI, P. K. (Journal of Soil and Water Conservation, 2021)
An incubation study on 20 representative basmati growing soils of Jammu was carried out for 15, 30, 45 and 60 days submergence to record changes in the availability of micronutrients (Zn, Cu, Fe and Mn). The soils under study were sufficient in DTPA extractable Cu, Fe and Mn, but 95% soil samples were deficient in Zn. The availability of Fe and Mn increased by 60-65% and 200-250% after 30 and 45 days of incubation, respectively whereas Zn and Cu decreased upto 34 & 74%, respectively. Both simple and multiple correlation and regression analysis showed variable contribution of physico-chemical properties. Management of Zn and Cu for better nutrition, production and productivity of famous basmati rice growing soils in rice-wheat agro-ecosystem of Jammu is needed